The integrated interdisciplinary vocational training of the future experts from book design in VUZ (Pedagogy of Higher and Secondary Education, 2006)
The article is devoted to the issue of integrated interdisciplinary future book-design experts training m the higher educational institutions. Such preparation should be earned out through the interrelation of methodical fundamental, professional and special disciplines on a design basis.
Keywords: book the schedule; design of the book; interdisciplinary preparation; cycle of professional disciplines